스파의 서비스품질이 관계몰입과 고객만족에 미치는 영향 - 서혜원; Hae-won Seo; 이인희; In-hee Lee (한국미용학회지, 2021)
This study researched the effects of service quality of spa on the relational commitment and customer satisfaction. For this, the main survey was conducted targeting the customers using hotel spa and brand spa in Seoul, capital area, and Jeju-do, from January 14 th 2020 to February 11 th 2020. After distributing total 400 questionnaires, total 347 questionnaires were used for the final analysis by excluding 53 questionnaires with insincere responses. The results of this study are as follows. First, in the results of understanding the demographic characteristics of research subjects, there were many women in sex, many subjects in their 30-39 in age, and many married subjects in the marital status. In the highest level of education, the graduation from university was the most. In the monthly average income, the 3 million-5 million won was the most while the office job was the most in occupation. Second, in the effects of service quality of spa on the relational commitment, the subfactors of service quality such as assurance, empathy, and reliability were the important factors on customers’ affective commitment. The subfactors of service quality such as empathy, assurance, and tangibles were the important factors on customers’ calculative commitment. Third, in the effects of service quality of spa on the customer satisfaction, the subfactors of service quality such as assurance, responsiveness, reliability, and empathy had significant effects on the customer satisfaction. Fourth, in the effects of relational commitment on the customer satisfaction, the subfactors of relational commitment such as customers’ affective commitment and customers’ calculative commitment had significant effects on the customer satisfaction. The results of this study showed that the service quality of spa would be an important factor for the improvement of relational commitment and customer satisfaction.